The synthesis and biological evaluation of a new bioactive metabolite of mosapride as a potential gastroprokinetic agent. (January 2019) - Yao, Jiaxin; Li, Kunjie; Song, Yufeng; He, Zhonggui; Liu, Zheng; Zhao, Longshan; Wang, Shaojie
Aim: To synthesize the new bioactive metabolites of mosapride (R)-N-[2-hydroxy-3-(4-fluorobenzyl)amino]-propyl-5-chlorine-4-amino-2-ethoxyben-zamide (R-isomer) and (S)-N-[2-hydroxy-3-(4-fluorobenzyl)amino]-propyl-5-chlorine-4-amino-2-ethoxybenzamide (S-isomer) and evaluate their in vitro and in vivo pharmacological and pharmacokinetic profiles.Results: S-isomer as a gastroprokinetic agent showed significant pharmacological activities in vivo . Furthermore, compared with the EC50 values for R-isomer and mosapride, S-isomer was proven to generate the same 5-HT4 receptor agonistic activity with a smaller amount. S-isomer exhibited significant differences in the pharmacokinetic properties, which indicate that higher absorption rate and extent compared with R-isomer.Conclusion: S-isomer might have great potential as a safe and effective prokinetic agent capable of lessening gastrointestinal symptoms and increasing quality of life.